1999
DOI: 10.1093/intimm/11.10.1709
|View full text |Cite
|
Sign up to set email alerts
|

The Ig heavy chain intronic enhancer core region is necessary and sufficient to promote efficient class switch recombination

Abstract: The intronic IgH enhancer E(mu), which consists of the core enhancer (cE(mu) flanked by 5' and 3' matrix attachment regions (MAR), has been implicated in the control of IgH locus recombination and transcription. Both cE(mu) and the MAR are required to enhance transcription of an IgH transgene. To elucidate the regulatory functions of cE(mu) versus its associated MAR in IgH class switch recombination (CSR), we have assayed ES cell lines which have targeted deletions of these elements, both individually and in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
28
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 45 publications
7
28
1
Order By: Relevance
“…Although some noticeable effects of Em deletion on CSR efficiency have been previously reported, it is admitted that Em is dispensable for such a process in vivo (13,19,20,58). Because our full-length Em KO model modified peripheral B cell fate, we expected Ab responses to be affected.…”
Section: Discussionmentioning
confidence: 92%
“…Although some noticeable effects of Em deletion on CSR efficiency have been previously reported, it is admitted that Em is dispensable for such a process in vivo (13,19,20,58). Because our full-length Em KO model modified peripheral B cell fate, we expected Ab responses to be affected.…”
Section: Discussionmentioning
confidence: 92%
“…The activity of enhancer elements within the 3Ј IgH RR (hs3b and hs4) is required to activate transcription from promoters flanking S regions (I promoters) of downstream C H genes and, thereby, regulates CSR (2,18). Based on location, iE was a candidate to transcriptionally activate S during CSR; correspondingly, deletion of this element appeared to result in a decrease in IgH CSR (19,20). However, the exact mechanism by which deletion of iE affects CSR remains unclear.…”
mentioning
confidence: 99%
“…1A). The first of these to be identified was the ϳ1-kb intronic enhancer E, which is situated in the intron between J H and C Targeted deletion studies with mice have revealed that E is important for VDJ joining (1,29,32,36).A 3Ј regulatory region (3Ј RR) extends ϳ35 kb downstream of the C␣ gene and includes multiple DNase I-hypersensitive (hs) sites. The murine 3Ј RR contains modules (Fig.…”
mentioning
confidence: 99%